Clinical Evaluation of NIKS-Based Bioengineered Skin Substitute Tissue in Complex Skin Defects: Phase I/IIa Clinical Trial Results - Schurr, Michael J. (Mary Ann Liebert, Inc., 2012)
BACKGROUND: Complex skin defects, such as burns and acute cutaneous trauma, are life-threatening injuries, often requiring temporary allograft placement to maintain fluid homeostasis and prevent infection until permanent wound closure is possible. THE PROBLEM: The current standard of care for the management of full-thickness wounds that are unable to be closed in a single surgical stage is temporary coverage with cadaver allograft until an acceptable wound bed has been established. This approach has limitations including limited availability of human cadaver skin, the risk of disease transmission from cadaveric grafts, and inconsistent cadaver allograft quality. BASIC/CLINICAL SCIENCE: Near-diploid neonatal human keratinocyte cell line (NIKS)-based human skin tissue is a full-thickness, living human skin substitute composed of a dermal analog containing normal human dermal fibroblasts and a fully-stratified, biologically and metabolically active epidermis generated from NIKS keratinocytes, a consistent and unlimited source of pathogen-free human epidermal progenitor cells. CLINICAL CARE RELEVANCE: NIKS-based human skin tissue is a living bioengineered skin substitute (BSS) intended to provide immediate wound coverage and promote wound healing through sustained expression by living cells of wound healing factors. CONCLUSION: A phase I/IIa clinical trial found that NIKS-based BSS was well tolerated and comparable to cadaver allograft in the ability to prepare full-thickness complex skin defects prior to autografting. There were no deaths and no adverse events (AE) associated with this BSS. Exposure of the study subjects to the skin substitute tissue did not elicit detectable immune responses. Notably, this tissue remained viable and adherent in the wound bed for at least 7 days.